2021
DOI: 10.1029/2020gl092169
|View full text |Cite
|
Sign up to set email alerts
|

First Simultaneous Observation of STEVE and SAR Arc Combining Data From Citizen Scientists, 630.0 nm All‐Sky Images, and Satellites

Abstract: The subauroral region, located equatorward from typical auroral displays, has been extensively studied by investigating processes like subauroral polarization streams (SAPS), subauroral ion drifts (SAIDs), and stable auroral red (SAR) arcs. Recently a new optical phenomenon known as strong thermal emission velocity enhancement (STEVE) has brought renewed interest in this region (Gallardo-Lacourt, Liang, et al.,2018;MacDonald et al., 2018). A handful of papers have reported characteristics of STEVEs that seem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The symbols representing the peaks in N e , T e , and V hor do not fall on top of the arc, which is evidence of a potential change in the height of the emission. A lower altitude emission might be more appropriate and consistent with a SAR arc that has evolved into STEVE, since the latter has been observed to occur at altitudes between ∼170 and 300 km (Archer, St.‐Maurice, et al., 2019; Liang et al., 2019; Martinis et al., 2021) and not near 425 km.…”
Section: Data and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The symbols representing the peaks in N e , T e , and V hor do not fall on top of the arc, which is evidence of a potential change in the height of the emission. A lower altitude emission might be more appropriate and consistent with a SAR arc that has evolved into STEVE, since the latter has been observed to occur at altitudes between ∼170 and 300 km (Archer, St.‐Maurice, et al., 2019; Liang et al., 2019; Martinis et al., 2021) and not near 425 km.…”
Section: Data and Discussionmentioning
confidence: 91%
“…This mechanism requires a minimum of ∼3 eV, equivalent to 4.4 km/s for NO + (the dominant ion in SAIDs), thus explaining why STEVE is observed during intense SAIDs. Some studies have shown that STEVEs and SAR arcs can occur simultaneously while observed at different geographic locations (Martinis et al., 2021) or that STEVE can merge with a preexisting SAR arc (Liang et al., 2019). However, available observations have never allowed the examination of whether a SAR arc can evolve into STEVE (or vice versa).…”
Section: Introductionmentioning
confidence: 99%
“…While optically different, SAR arcs and STEVE present many similarities with respect to timescales and geophysical location; therefore, it is important to study if a relationship between these two structures could be established. Previous studies reported observations of STEVE and SAR arcs located temporally and spatially near but not collocated (e.g., Chu et al., 2019; Liang et al., 2019; Martinis et al., 2021); however, they were not able to demonstrate if these two structures were connected. More recently, a study by Martinis et al.…”
Section: Introductionmentioning
confidence: 90%
“…Limited investigations have shown that STEVE can occur after the proton aurora (Nishimura et al, 2020b) and that a SAR arc can transition to STEVE (Martinis et al, 2022). Subauroral emissions are not exclusive to each other, but STEVE and a SAR arc can be adjacent to each other simultaneously (Liang et al, 2019;Chu et al, 2019;Martinis et al, 2021). The proton aurora and red arc that transitions to a SAR arc later have also been reported to co-exist during substorms (Nishimura et al, 2022b).…”
Section: Chemistry and Emission Mechanismsmentioning
confidence: 99%